REVIEW: ILOILOâ€™S BALUT INDUSTRY (PHILIPPINES)-AN EXPLORATION OF THE ENVIRONMENT, SOCIAL ORGANIZATIONS, AND CONSUMER DEMANDS - De Vergara, Tisha Isabelle; Alejandria, Maria Carinnes; Lustañas, Bridgette (Asian Journal of Agriculture, 2020)
Abstract. Vergara TID, Alejandria MC, Lustanas B. 2020. Review: Iloilo?s Balut Industry (Philippines)-An exploration of the environment, social organizations, and consumer demands. Asian J Agric 3: 41-51. The province of Iloilo has one of the highest numbers of small scale duck farms in the country. Its agricultural landscape has allowed the rise of farmers entering duck raising practices mainly along rice fields throughout the province. However, continuous interventions on the agricultural sector of Iloilo are directed at boosting economic growth. This paper provides a qualitative evaluation of the efficiency of current policies and implementation of rules and regulations on the duck and duck egg industry of the Province of Iloilo. Findings revealed the need to address issues on the production, distribution, and marketing of the duck and duck egg products of the province. Environmental conditions such as climate and water access, along with the role of social organizations, and impact of existing policies play a key role in the current trajectory of the Iloilo duck industry.